Effect of alirocumab and evolocumab on all-cause mortality and major cardiovascular events: A meta-analysis focusing on the number needed to treat - Wang, Hong-Fei; Mao, Yu-Cheng; Xu, Xin-Yi; Zhao, Si-Yu; Han, Dan-Dan; Ge, Shi-Yao; Song, Kai; Geng, Chang; Tian, Qing-Bao (Frontiers in Cardiovascular Medicine, 2022)
Aims The efficacy of anti-proprotein convertase subtilisin/Kexin type 9 (PCSK9) monoclonal antibodies in patients with atherosclerotic cardiovascular disease (ASCVD) remains unclear. Therefore, this study aims to assess the effect of PCSK9 inhibitors (alirocumab and evolocumab) on ASCVD patients considering the number needed to treat (NNT). Methods We reviewed randomized controlled trials (RCTs) which compared the effects of alirocumab or evolocumab and placebo or standards of care. All articles were published in English up to May 2022. Using random effect models, we estimated risk ratios (RRs), NNT, and 95% confidence intervals (CI). Results We incorporated 12 RCTs with 53 486 patients total, of which 27 674 received PCSK9 inhibitors and 25 812 received placebos. The mean follow-up duration was 1.56 years. The effect of PCSK9 inhibitors on major adverse cardiovascular events (MACE) was statistically significant, and the corresponding mean NNT was 36. Alirocumab reduced the risk of MACE, stroke, and coronary revascularization; the corresponding mean NNT were 37, 319, and 107, respectively. Evolocumab positively affected MACE, myocardial infarction, stroke, and coronary revascularization; the corresponding mean NNT were 32, 78, 267, and 65, respectively. The effects of alirocumab or evolocumab on all-cause mortality and cardiovascular mortality were not statistically significant. Conclusion This study suggests that preventing one patient from MACE needed to treat 36 patients with ASCVD with PCSK9 inhibitors for 1.56 years. Both alirocumab and evolocumab reduced MACE, stroke, and coronary revascularization. Evolocumab had a positive effect on myocardial infarction, but no effects were noted for alirocumab. In addition, alirocumab may not be as effective as evolocumab. NNT visualizes the magnitude of efficacy to assist in clinical decisions. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=344908], identifier [CRD42022344908].